The role of sustainable finance in achieving Sustainable Development Goals: does it work? - Ziolo, Magdalena; Bak, Iwona; Cheba, Katarzyna (Technological and Economic Development of Economy, 2021)
The World Bank and International Monetary Fund reported that the achievement of the 17 Sustainable Development Goals (SDGs) requires an escalation of development finance. The report Scaling Finance for the Sustainable Development Goals highlighted the urgency of the efforts to realize SDGs in encouraging financial innovation to move quickly. Even if the role of finance in achieving SDGs is unquestionable, few scientific studies have addressed these issues. We tried to fill the existing research gap. In this study, we examined the link between sustainable finance and SDGs based on European Union countries belonging to the OECD. We present a new and the original research approach. We assumed that the sustainable finance model plays a fundamental role in implementing SDGs (all SDGs were analysed except for SDG 6 and SDG14, due to lack of statistics were not analysed) and ensuring that social and environmental sustainability are reflected in SDGs. The results of this study show that the more sustainable the finance model, the better the achievement of SDGs in the group of analysed countries. We found a strong link between sustainable finance model and social sustainability (SDG1, 3, 4, 5, 10, 16); environmental sustainability (SDG11, 12, 13, 15) and economic sustainability (SDG8, 9, 17).First published online 3 December 2020